2002
DOI: 10.1007/s102670200017
|View full text |Cite
|
Sign up to set email alerts
|

The constitution of incompatibility factor and mating characteristics of spore isolates in a bipolar mushroom, Pholiota nameko

Abstract: Pholiota nameko is a wood-rotting edible mushroom that carries a bipolar A incompatibility factor gene. The linkage analysis of the multiple allelomorphic A factor gene demonstrated that sexual reproduction produced a monospore isolate carrying a new A factor gene in addition to two parental mating types of isolates. However, 10%-30% of the modified monospore isolates could not produce a dikaryon with both of the parental monokaryons by crossing. It is concluded that the bipolar A incompatibility factor gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Although Pholiota microspora (P. nameko, Strophariaceae) has a very similar life cycle to other members of the order Agaricales, such as the tetrapolar mushroom C. cinerea, it has a bipolar A incompatibility factor and at least six different mating types (29). Ratanatragooldacha et al (29) concluded that the bipolar A locus of P. microspora contains two functional subunits, A␣ and A␤, which appear to be located 0.3 centimorgan apart from each other on the same chromosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pholiota microspora (P. nameko, Strophariaceae) has a very similar life cycle to other members of the order Agaricales, such as the tetrapolar mushroom C. cinerea, it has a bipolar A incompatibility factor and at least six different mating types (29). Ratanatragooldacha et al (29) concluded that the bipolar A locus of P. microspora contains two functional subunits, A␣ and A␤, which appear to be located 0.3 centimorgan apart from each other on the same chromosome.…”
mentioning
confidence: 99%
“…Ratanatragooldacha et al (29) concluded that the bipolar A locus of P. microspora contains two functional subunits, A␣ and A␤, which appear to be located 0.3 centimorgan apart from each other on the same chromosome. Aimi et al (1) sequenced and characterized the P. microspora genes encoding the homeodomain protein, hox1, and the pheromone receptor, rcb1, which are putative homologues of the HD1 protein and putative pheromone receptor protein genes in the tetrapolar basidiomycete C. cinerea, respectively.…”
mentioning
confidence: 99%